Adapting a sexual and reproductive health program for Latina teens and their female caregivers: a qualitative study - Merrill, Katherine G.; Fuentes, Jacqueline; Merrill, Jamison; DeCelles, Jeff; Silva, Jacqueline; Sedeño, Angela; Salgado, Susana; Vargas, Sara; Cano, Jennifer K.; Nabor, Veronica; Rodriguez, Laura; Melgoza, Vanessa; et al. (Frontiers in Public Health, 2025)
BackgroundAdaptation is widely recognized as important when interventions are to be delivered in new settings or with new populations. However, there are gaps in the literature on how adaptations are carried out and documented. IMARA is a 12-h evidence-based sexual health intervention for Black teens and their mothers, designed for delivery over two days. We present our systematic process of adapting IMARA for Latinas to produce the Floreciendo (“Blooming”) program for Latina teens (14–18 years old) and their female caregivers (e.g., mothers, sisters).MethodsUsing a community-based participatory research (CBPR) approach, we carried out a qualitative study that included 7 focus groups: 4 with staff from community partner organizations (n = 29), 2 with Latina teens (14–18 years) (n = 11), and 1 with female caregivers (n = 5). We also conducted seven key informant interviews with experts in sexual health and Latina health. We used Escoffery’s recommended steps to guide our adaptation process. Data were thematically coded and adaptations documented using the FRAME for reporting modifications to evidence-based interventions.ResultsInformed by the data, we grouped IMARA content into four sessions for Floreciendo, each with unique curricular content and designed to be delivered in two hours (eight hours total): (1) Foundations in Sexual Risk Prevention; (2) Condoms and Contraception; (3) Family Strengthening; and (4) Gender and Relationships. We documented adaptations made for each session. For example, participants emphasized unplanned pregnancy as an important issue facing Latina teens. In response, we added an activity providing hands-on experience with contraceptive methods. Participants also highlighted how gender norms and family expectations in Latine culture shape Latina teens’ sexual and reproductive health practices. We therefore developed activities and opportunities for discussion addressing these cultural influences. We removed IMARA activities considered of lower priority (e.g., portrayal of women in the media).ConclusionThis study addresses gaps in the literature by reporting in detail the adaptations we made to an evidence-based intervention using qualitative methods. The four curriculum sessions we generated through our adaptation process will form the basis of the intervention components we will test in future work using the multiphase optimization strategy (MOST) framework.